Retrospective sequence analysis of the human PRNP gene from the formaldehyde-fixed paraffin-embedded tissues: report of two cases of Creutzfeldt-Jakob disease - Sikora, J; Srbová, A; Koukolík, F; Matej, R (Folia microbiologica, 2006)
The definitive diagnosis of the CJD (Creutzfeldt-Jakob disease; very rare neurodegenerative disorder) can be established only on the basis of post-mortem examination of the central nervous system tissue. Formaldehyde-fixed paraffin-embedded (FFPE) tissue samples may thus constitute the only material available for molecular pathology analyses. We performed post-mortem analysis of the coding region of the prion-protein gene (PRNP)-sequence variations in two definite CJD cases suggestive of genetic form. Only FFPE tissues were available for molecular analyses. The PRNP gene open reading frame was amplified from the genomic DNA (FFPE isolated) in four overlapping, two round semi-nested PCR products that were directly sequenced. We found known pathogenic sequence variation g.532 G>A (Asp178Asn) in patient 1 but we did not find any pathogenic sequence variation in patient 2 despite her origin from the Slovak Orava region. Based on these results, we were able to discriminate between genetic and sporadic form of CJD in patient 1 and 2, respectively. The established method was found to be efficient for the sequence-variation analysis of the entire PRNP gene coding region using the genomic DNA isolated from the FFPE tissues; it can be employed in other retrospective molecular studies.
Keywords: Male; fixace tkání; polymerázová řetězová reakce; lidé středního věku; Polymerase Chain Reaction; Prions; retrospektivní studie; Prion Proteins; Humans; Middle Aged; Molecular Diagnostic Techniques; senioři; Paraffin Embedding; mužské pohlaví; Female; Amino Acid Substitution; Sequence Analysis, DNA; Aged; polymorfismus genetický; ženské pohlaví; Retrospective Studies; prionová bílkovina; Open Reading Frames; Creutzfeldtova-Jakobova nemoc; Polymorphism, Genetic; Tissue Fixation; sekvenční analýza DNA; diagnostické techniky molekulární; otevřené čtecí rámce; Creutzfeldt-Jakob Syndrome; lidé; substituce aminokyselin; zalévání tkání do parafínu; priony